Factors Influence MSME's Switching Behavior in Digital Marketing Channel: Evidence from Indonesia - Agustina, Tri Siwi; Suwardianto, Rico Adi Suwardianto; Jamali, Muhebullah (Universitas Airlangga, 2024)
In realizing digital-based services and the application of people's economy, the Surabaya, Indonesia. The government has launched a website called E-Peken. It is hoped that the presence of digital marketing infrastructure can help MSME actors increase their business potential by expanding the marketing reach of their superior products. This study aims to determine the desire to switch to e-commerce regarding the failure of e-commerce services and the experience of using the E-Peken website. The research method used was quantitative with data collection through observation and questionnaires on 346 MSMEs in Surabaya City who were recorded as users of the E-Peken website. The results obtained show that the failure of e-commerce services has proven to affect switching intentions; usage experience is proven to affect switching intentions and switching intentions are proven to affect switching behavior from E-Peken to other e-commerce. In this manner, it is suggested that assist investigation include mediating or moderating variables. Managerial suggestions that can be submitted to the Surabaya Government as the E-Peken site service provider are to make strides in administrations on a progressing premise and continuously react to the desires of MSME's players as users.